2018
DOI: 10.1371/journal.pone.0190120
|View full text |Cite
|
Sign up to set email alerts
|

Reduced telomere length is associated with fibrotic joint disease suggesting that impaired telomere repair contributes to joint fibrosis

Abstract: ObjectiveJoint fibrosis affects many synovial joints (including hip, knee and shoulder) causing stiffness and pain. The mechanism of joint fibrosis remains unknown, although genetic factors may contribute. Defects in maintenance of telomere length resulting from impaired telomere repair have been shown to cause lung and liver fibrotic disease. Here we tested the hypothesis that joint fibrosis and other soft tissue fibrotic conditions are also associated with telomere length.Patients and methods5,200 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Kalson et al. [ 28 ] studied the mean leukocyte telomere length (LTL) in a cohort study which checked for the correlation between joint fibrosis and telomeres. The authors concluded that in patients with adhesive capsulitis an altered telomere length was present and it could lead to severe tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kalson et al. [ 28 ] studied the mean leukocyte telomere length (LTL) in a cohort study which checked for the correlation between joint fibrosis and telomeres. The authors concluded that in patients with adhesive capsulitis an altered telomere length was present and it could lead to severe tissue fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A short telomere length is suggested to be associated with, or predict, many common aging diseases, including various geriatric diseases, such as cancer, dementia, and osteoporosis [1,4]. Furthermore, in a prospective study by Goglin et al [5], an increase in telomere length resulted in a lower mortality rate, while a decrease in telomere length resulted in a higher mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Approximated five percent of patients suffer stiffness as a significant complication after their TKA [ 6 ], and some require manipulation under anaesthesia [ 22 ] or revision surgery because of persistent stiffness [ 18 ]. Stiffness after knee arthroplasty may have a genetic component and epidemiological studies have found chromosomal changes in those reporting such symptoms [ 14 ], with an increased understanding of the biological basis for such a host response [ 16 ]. This is leading to a greater awareness that stiffness is potentially avoidable both from a mechanical and biological perspective [ 6 ].…”
Section: Introductionmentioning
confidence: 99%